Plano Nacional de Educação e qualidade de ensino: considerações sobre a autoeficácia dos agentes escolares - Miguel Henrique Russo; Roberta Gurgel Azzi (EccoS – Revista Científica)
Ref lection motivated by the approval of the National Education Plan (PNE) and the expectation that it brings as legal and methodological tool for the improvement of national education. The objective is to question whether the PNE contains the elements that lead to better education and does so in terms that are independent of agents to define their actions. The goals and strategies of the PNE, that have better education as an objective, are presented and discussed. Given the generality and the focus of those, it is concluded that will require new readings about them will be required in state and municipal plans. The discussion is focused on the issue of teachers health, which is shown in strategy 7 . 31 , and on its confrontation with the aid of the construction of self-efficacy.